2001
DOI: 10.4049/jimmunol.166.1.662
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation-Dependent Modulation of Experimental Autoimmune Encephalomyelitis by Ligand Stimulation of Vα14 NK T Cells

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a Th1 cell-mediated autoimmune disease that can be protected against by stimulating regulatory cells. Here we examined whether EAE can be purposefully modulated by stimulating Vα14 NK T cells with the CD1d-restricted ligand α-galactosylceramide (α-GC). EAE induced in wild-type C57BL/6 (B6) mice was not appreciably altered by injection of α-GC. However, EAE induced in IL-4 knockout mice and IFN-γ knockout mice was enhanced or suppressed by α-GC, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…This was associated with a striking inhibition of antigen-specific IFN-γ production, but was independent of IL-4 [89]. Additionally, studies using α-GalCer induced NKT cell stimulation confirmed the capacity of NKT cells to modulate the disease by inducing Th2 cytokine profiles [90,91,92]. However, others reported that the protective effect was associated with an enhanced IFN-γ production by liver-confined NKT cells [92].…”
Section: Experimental Autoimmune Encephalomyelitis and Multiple Sclermentioning
confidence: 92%
See 2 more Smart Citations
“…This was associated with a striking inhibition of antigen-specific IFN-γ production, but was independent of IL-4 [89]. Additionally, studies using α-GalCer induced NKT cell stimulation confirmed the capacity of NKT cells to modulate the disease by inducing Th2 cytokine profiles [90,91,92]. However, others reported that the protective effect was associated with an enhanced IFN-γ production by liver-confined NKT cells [92].…”
Section: Experimental Autoimmune Encephalomyelitis and Multiple Sclermentioning
confidence: 92%
“…Furthermore, the efficacy of α-GalCer treatment depended on the administration route, timing and dose [93,92]. In an effort to overcome these problems, combination therapy of α-GalCer and CD86 blocking antibodies or treatment with OCH was shown to selectively induce a Th2 response by the NKT cells and resulted in a reduced development of EAE [91,94,40].…”
Section: Experimental Autoimmune Encephalomyelitis and Multiple Sclermentioning
confidence: 99%
See 1 more Smart Citation
“…However, their contribution to EAE is unknown while the role of IFN-c or IL-4 producing NKT cells has been investigated in EAE. Depending on the timing and mode of their activation with aGalCer, NKT cells can exacerbate EAE [163] or downmodulate the inflammatory response [163][164][165][166]. While NKT cells home to secondary lymphoid tissue, gut associated lymphoid tissue, and liver, recruitment to the CNS is under debate [162,167,168].…”
Section: Plasticity Of T Helper Cells In Eaementioning
confidence: 99%
“…Several reports suggest that these CD28-CD80/86-and CD154-CD40-mediated costimulatory pathways might be involved in IFN-c/IL-4 production by a-GalCer-stimulated NKT cells [14,15]. If IL-18 pretreatment affects the expression level of these costimulatory molecules, the downstream signals may regulate NKT cell function by modulating IFN-c/IL-4 production.…”
Section: Introductionmentioning
confidence: 99%